An approach to smart working in Italy - Rojas Valentino, Irving Aldo (2020)
It has long been introduced into the field of work. As a result, smart working appeared a few years ago in Italy as a mode of execution of the contract labour in a  subordinate employment  relationship. As with all novelties, this has given rise to great expectations, but it has also revealed points of controversy that are gradually becoming clearer. This new labour contracting tool aims, directly and indirectly, to renew, update and adapt the historical institutions of Labour Law to an increasingly flexible labour market. Smart working seeks to become an important technological innovation within the employment contract, modifying concepts that until a few decades ago seemed indisputable.